SUBJECT SCOPE AND ARTISTRY OF N. FOZILOV’S STORIES (World Bulletin of Social Sciences, 2023)
As a result of this small research, we have considered the comments on the theme and art of the stories of Nasir Fazilov, one of the great representatives of Uzbek children's literature.
Keywords: story; household stories; prototype; image